Haptic Technology Intelligent Approach to Future Man-Machine Interaction - Hoirul Basori, Ahmad; Malebary, Sharaf J.; Barukab, Omar M. (IntechOpen, 2022)
These days, people's desire for an evolutionary interface is strong. The new model of human-machine interaction is expected to be more realistic and immersive. Haptic technology plays a key role in this regard. It can be used for medical, robotics, and digital heritage applications. Over three sections and five chapters, this book examines these potential uses of haptics. Chapters discuss using haptic feedback to improve robotic perception, for medical simulations, and to enhance digital heritage documentation.